2018
DOI: 10.1371/journal.pone.0194314
|View full text |Cite
|
Sign up to set email alerts
|

Organic cultivation of Ashwagandha with improved biomass and high content of active Withanolides: Use of Vermicompost

Abstract: Withania somnifera (Ashwagandha) has recently been studied extensively for its health-supplementing and therapeutic activities against a variety of ailments. Several independent studies have experimentally demonstrated pharmaceutical potential of its active Withanolides, Withaferin A (Wi-A), Withanone (Wi-N) and Withanolide A (Wil-A). However, to promote its use in herbal industry, an environmentally sustainable cultivation and high yield are warranted. In modern agriculture strategies, there has been indiscri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…In a study conducted on Withania somnifera (Ashwagandha), utilization of vermicompost has been found to be beneficial in improving germination, plant growth, yield, and content of bioactive Withanolides of the Ashwagandha leaves [27]. This is in line with the findings of the current study where the addition of vermicompost was found to significantly elevate the amounts of bioactive compounds in the pineapple fruits, compared to control.…”
Section: Discussionsupporting
confidence: 90%
“…In a study conducted on Withania somnifera (Ashwagandha), utilization of vermicompost has been found to be beneficial in improving germination, plant growth, yield, and content of bioactive Withanolides of the Ashwagandha leaves [27]. This is in line with the findings of the current study where the addition of vermicompost was found to significantly elevate the amounts of bioactive compounds in the pineapple fruits, compared to control.…”
Section: Discussionsupporting
confidence: 90%
“…We have earlier optimized the extraction of two of the major withanolides- Withaferin-A and Withanone using cyclodextrin [60] . As reported earlier, leaves possess highest content of withanolides; whereas stem possesses a relatively high ratio of Withanone [60] , [61] . We prepared leaf and stem extracts [60] , and investigated the content of 8 withanolides.…”
Section: Resultssupporting
confidence: 73%
“…The species W. coagulans is highly acclaimed in the Indian ayurvedic system of medicine, where it is known for its medicinal significance in promoting physical and mental health [26,27]. Its active components include alkaloids, steroidal compounds, lactones, withaferin a [28], withanoloids [29], withanone [30], etc. that act as anti-inflammatory, anticancer, chemoprotective, hepatoprotective, immune modulatory, antifungal, antibacterial, hypocholestroemic, and radical scavenging agents [31].…”
Section: Resultsmentioning
confidence: 99%